3D-modeling of the Skellefte district using electrical, potential field and reflection-seismic data : A basis for 4D-modeling of mineral belts - Tavakoli, Saman (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2011)
As a part of a 4D modeling project, two studies with different scopes were conducted in the central Skellefte district (CSD), northern Sweden. The aim of the studies is to create a basis for a better understanding of the spatial relationship between geological structures and mineralization and to construct a 3D and 4D geology model of the area.In the first study, we used geo-electrical data to define the geological structures at depth down to 430 m. The inversion of the resistivity and Induced Polarization (IP) data indicated a number of lithological contacts, which required further constraints prior to constructing the final 3D model.Hence we measured petrophysical properties including density, magnetic susceptibility, resistivity and IP of 154 samples, selected from drill-holes in vicinity of the resistivity/ IP profiles, to constrain the model. Forward resistivity models were then acquired using the resistivities measured on drillcores, to test the response of different geological scenarios in 3D after inversion. The gravity and magnetic response of the resistivity/ IP models was then calculated to constrain the models down to 1.5 km depth. The models were then modified, until reaching a consistency between geo-electrical and potential field data. The result indicated the possibility of three sulphide mineralization zones within the highly conductive parts at depth ≤ 500 m. The result also helped to determine the geometry of the contact between sedimentary rocks of the Vargfors basin and volcanic rocks of the Skellefte Group.In the second study, we tested geological models based on interpretation of reflection- seismic data using potential field data (down to 5 km depth) as well as electrical data (down to 430 m depth). The gravity and magnetic data especially benefitted the interpretation where no reflector is indicated, or poor-quality reflectors could not contribute to the understanding of major lithological contacts along the main faults and shear zones in the CSD. Moreover, the gravity and magnetic data, ...